Quality control on mononuclear cells collected for extracorporeal photochemotherapy: comparison between two UV‐A irradiation devices. Issue 4 (14th May 2015) - Cervio, M.; Scudeller, L.; Viarengo, G.; Del Fante, C.; Perotti, C.
<x xml:space="preserve">Abstract</x> Recently, MacoPharma released a new UV‐A cell irradiator device (Macogenic G2) for extracorporeal photopheresis (ECP), smaller and lighter than the Macogenic G1 but with no integrated cooling system. We compared the two devices at different working temperatures (G1 at standard irradiation temperature – 21°C – and G2 set by purpose at 34°C) in patients affected with chronic graft‐versus‐host disease and chronic lung allograft dysfunction treated by ECP. We demonstrate that both G1 and G2 devices are efficient in inducing the inhibition of lymphocytic proliferation and mononuclear cells apoptosis after 48 h even when G2 is set at higher‐than‐standard temperature.